The hrpZ Gene of Pseudomonas syringae pv. phaseolicola Enhances Resistance to Rhizomania Disease in Transgenic Nicotiana benthamiana and Sugar Beet - Pavli, Ourania I. (Public Library of Science, 2011)
To explore possible sources of transgenic resistance to the rhizomania-causing Beet necrotic yellow vein virus (BNYVV), Nicotiana benthamiana plants were constructed to express the harpin of Pseudomonas syringae pv. phaseolicola (HrpZ(Psph)). The HrpZ protein was expressed as an N-terminal fusion to the PR1 signal peptide (SP/HrpZ) to direct harpin accumulation to the plant apoplast. Transgene integration was verified by mPCR in all primary transformants (T0), while immunoblot analysis confirmed that the protein HrpZ(Psph) was produced and the signal peptide was properly processed. Neither T0 plants nor selfed progeny (T1) showed macroscopically visible necrosis or any other macroscopic phenotypes. However, plants expressing the SP/HrpZ(Psph) showed increased vigor and grew faster in comparison with non-transgenic control plants. Transgenic resistance was assessed after challenge inoculation with BNYVV on T1 progeny by scoring of disease symptoms and by DAS-ELISA at 20 and 30 dpi. Transgenic and control lines showed significant differences in terms of the number of plants that became infected, the timing of infection and the disease symptoms displayed. Plants expressing the SP/HrpZ(Psph) developed localized leaf necrosis in the infection area and had enhanced resistance upon challenge with BNYVV. In order to evaluate the SP/HrpZ-based resistance in the sugar beet host, A. rhizogenes-mediated root transformation was exploited as a transgene expression platform. Upon BNYVV inoculation, transgenic sugar beet hairy roots showed high level of BNYVV resistance. In contrast, the aerial non-transgenic parts of the same seedlings had virus titers that were comparable to those of the seedlings that were untransformed or transformed with wild type R1000 cells. These findings indicate that the transgenically expressed SP/HrpZ protein results in enhanced rhizomania resistance both in a model plant and sugar beet, the natural host of BNYVV. Possible molecular mechanisms underlying the enhanced resistance and plant growth phenotypes observed in SP/HrpZ transgenic plants are discussed.